Supporting interaction in the context of residential child care - Kirsi Tuomi (Scottish Journal of Residential Child Care)
This article reflects on the use of one type of therapy, called Theraplay, in building attachments in residential child care in one agency in Finland. The purpose is to examine the role of this therapy in helping to heal relationships in the residential centre before the child moves on to a foster home. Nikinharjun kuntayhtyma is a joint municipal authority in Hyvinkaa in Southern Finland. Nikinharju Child Care Centre has two units for short-term placements and assessment. Other services provided by the centre include family work, both within and outwith the centre, therapy services like Theraplay, music therapy and family therapy, supported living services for adolescents and a crisis residential service. The philosophy of the centre is based on attachment theory (Bowlby, 1988) but different approaches including psychodynamic and short term therapeutic approaches are also available depending on the situation of the child.